Does pituitary suppression affect live birth rate in women with congenital hypogonadotrophic hypogonadism undergoing intra-cytoplasmic sperm injection? A multicenter cohort study. (2nd September 2017) - Mumusoglu, Sezcan; Ata, Baris; Turan, Volkan; Demir, Berfu; Kahyaoglu, Inci; Aslan, Kiper; Seyhan Ata, Ayse; Yilmaz, Bulent; Yakin, Kayhan; Avci, Berrin; Uncu, Gurkan; Bozdag, Gurkan
Abstract: In this retrospective multicenter cohort study, women with congenital hypogonadotrophic hypogonadism (CHH) ( n = 57) who underwent intra-cytoplasmic sperm injection in-between 2010–2014 were compared to age-matched controls with tubal factor infertility ( n = 114) to assess ovarian stimulation cycle and pregnancy outcomes. Live birth rates (LBRs) per started cycle were 31.6 and 24.6% in CHH and controls groups, respectively ( p = 0.36). Comparable success rates were also confirmed with the logistic regression analysis (OR: 1.44, 95% CI: 0.78–2.67, p = 0.24). Of the 57 women with CHH, 19 were stimulated with the gonadotropin-releasing hormone (GnRH) antagonist protocol, 13 with the long-GnRH-agonist protocol. Pituitary suppression (PS) was not employed in the remaining 25 cases. Compared to women with PS, women without PS had significantly higher embryo implantation rates (21.6 versus 52.6%, p = 0.03). Although there was a trend favoring no PS, LBRs (25.0 versus 40.0%, p = 0.26) per cycle were short of statistical significance. LBRs per cycle (57.1 versus 31.2%, p = 0.11) and miscarriage rates (11.1 versus 16.7%, p = 0.75) were similar between CHH women who were given estrogen + progesterone and progesterone alone to support the luteal phase. In conclusion, the optimal stimulation protocol appears to be exogenous gonadotropin stimulation alone, without PS, and progesterone-only luteal phase support in CHH patients.